The impact of the herd health interventions in small ruminants in low input production systems in Ethiopia - Moliso, Mesfin M.; Molla, W.; Arke, A.; Nana, T.; Zewudie, F.A.; Tibebu, A.; Haile, A.; Rekik, M.; Magnusson, U.; Wieland, Barbara; Knight-Jones, Theodore J.D. (Frontiers Media, 2024)
Introduction: Diseases have a negative impact on production and profitability of small ruminants. A good herd health program can decrease the number of sick animals and improve herd performance.